Understanding Facilitators and Challenges to Care Transition in Cardiac Rehabilitation: Perspectives and Assumptions of Healthcare Professionals - Maiken Bay Ravn; Connie Berthelsen; Thomas Maribo; Claus Vinther Nielsen; Charlotte Gjørup Pedersen; Charlotte Handberg (SAGE Publishing, 2023)
Cardiac rehabilitation is an essential part of treatment for patients with cardiovascular disease. Cardiac rehabilitation is increasingly organized outside hospital in community healthcare services. However, this transition may be challenging. The aim of this study was to examine assumptions and perspectives among healthcare professionals on how facilitators and challenges influence the transition from hospital to community healthcare services for patients in cardiac rehabilitation. The study followed the Interpretive Description methodology and data consisted of participant observations and focus group interviews. The analysis showed that despite structured guidelines aimed to support the collaboration, improvements could be made. Facilitators and challenges could occur in the collaboration between the healthcare professionals, in the collaboration with the patient, or because of the new reality for patients when diagnosed with cardiovascular disease.